2020
DOI: 10.1038/s41398-020-00945-9
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric changes in subcortical structures following repeated ketamine treatment in patients with major depressive disorder: a longitudinal analysis

Abstract: Abnormal subcortical structures have been associated with major depressive disorder (MDD) and could be reversed by antidepressant treatment. To date no study has examined the relationship between subcortical volumes and repeated ketamine treatment. The current study investigated volume changes in specific subcortical structures and hippocampal subfields after six ketamine infusions. Forty-four patients with MDD received six subanesthetic dose infusions of ketamine. Depressive symptoms were assessed and magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
(73 reference statements)
1
27
1
Order By: Relevance
“…This process is an elementary component of neuroplasticity (30,84). Research supports the proposition that functional and structural changes at spines and synapses are the basis of learning, memory, and cognitive flexibility (30,85,86).…”
Section: Ketamine and Synaptogenesismentioning
confidence: 72%
“…This process is an elementary component of neuroplasticity (30,84). Research supports the proposition that functional and structural changes at spines and synapses are the basis of learning, memory, and cognitive flexibility (30,85,86).…”
Section: Ketamine and Synaptogenesismentioning
confidence: 72%
“…Alternatively, the differences may have arisen due to the heavier use of other drugs in the ketamine users in our study. In contrast, a group studying the effect of intermittent ketamine for treatment of major depressive disorder reported increases in grey matter volume in amygdala and hippocampus (Zhou et al 2020). It is likely that the processes occurring when ketamine is used intermittently for the treatment of depression differ from chronic ketamine use in the setting of dependence or harmful use and may reflect the increases in dendritic spine formation that are hypothesised to underlie the antidepressant effects of ketamine, as supported by data from pre-clinical studies (Li et al 2010).…”
Section: Discussionmentioning
confidence: 87%
“…The side-effects of ketamine abuse or misuse (23), except addiction, include neurotoxicity, cognitive dysfunction, adverse events associated with mental status, psychotomimetic effects, uropathy effects, liver-gallbladder effects and cardiovascular events. Research has shown that chronic ketamine use may lead to brain atrophy, particularly during the time of brain development (24,25), and the anti-depressive effects may be associated with increases in brain area volume (20). But to our knowledge, we are the first to report a young adult suffering from severe brain atrophy after long-term abuse of ketamine.…”
Section: Discussionmentioning
confidence: 88%
“…Ketamine addiction is related to the interference of glutamate neurotransmission, which influences the establishment of the subcortical regions, such as nucleus accumbens, which is associated with addictive behaviours (18). Studies also show that there are specific antidepressant properties of glutamatergic medications targeting NMDA receptors (19,20) and effective reduction of suicidal ideation (5). Furthermore, a small dose of ketamine can relieve pain in advanced tumour patients (14,21,22), but side effects must be considered.…”
Section: Discussionmentioning
confidence: 99%